The Influence of Pronated Foot Posture on Knee Isokinetic Strength, Static and Dynamic Postural Stability in Healthy Young Individuals - Woochan Chun; Hee-su Kim; Sieun Park; Jihea Park; Seunghee Shim; Sookyoung Park (Korean Research Society of Physical Therapy, 2021)
Background: The foot is a complex body structure that plays an important role in static and dynamic situations. Previous studies have reported that altered foot posture might affect knee joint strength and postural stability, however their relationship still remains unclear. Objects: The purpose of this study was to identify whether pronated foot posture has an influence on knee isokinetic strength and static and dynamic postural stability. Methods: Forty healthy young males aged 18 to 26 years were included. Foot posture was evaluated using the Foot Posture Index-6 (FPI-6), and the subjects were divided into two groups according to their FPI-6 scores: a neutral foot group (n = 20, FPI-6 score 0 to +5) and a pronated foot group (n = 20, FPI-6 score +6 or more). Biodex Systems 3 isokinetic dynamometer was used to evaluate knee isokinetic strength and hamstring to quadriceps ratio at three angular velocities: 60°/sec, 90°/sec, and 180°/sec. The static and dynamic postural stability in a single-leg stance under the eyes-open and eyes-closed conditions were measured with a Biodex Balance System. Results: There were no significant differences between the groups in knee isokinetic strength and static postural stability (p > 0.05), but there was a significant difference in the medial- lateral stability index (MLSI) for dynamic postural stability under the eyes-closed condition (p = 0.022). The FPI-6 scores correlated significantly only with the dynamic overall stability index (OSI) and the MLSI (OSI: R = 0.344, p = 0.030; MLSI: R = 0.409, p = 0.009) under the eyesclosed condition. Conclusion: Participants with pronated foot had poorer medial-lateral dynamic stability under an eyes-closed condition than those without, and FPI-6 scores were moderately positively correlated with dynamic OSI and dynamic MLSI under the eyes-closed condition. These results suggest that pronated foot posture could induce a change in postural stability, but not in knee isokinetic strength.